Caracterización agro socio económica de productores de papa (solanum tuberosum) involucrados en el proyecto fiasa-iniap, semillas andinas, en las provincias de Pichincha, Cotopaxi y Tungurahua 22-23. - Revelo Endara, Nataly Johanna (2023)
This project was developed in Pichincha, Cotopaxi, and Tungurahua provinces for the potato producers (Solanum tuberosum) belonging to the Ecuadorian Sierra due to the lack of knowledge regarding the agro-socio-economic conditions of the areas mentioned above in agreement with the National Institute for Agricultural Research (INIAP), and the Agrobiodiversity, Seeds and Sustainable Agriculture Research Fund (FIASA) since there is no evidence of improvements in the dynamics of life and production of the inhabitants of these sectors, therefore, this research has as its primary objective to build a database to characterize the social, economic, and productive situation of potato producers, for which the DRP Methodology (Participatory Rural Diagnosis) was used, which consists of collecting information with the social, economic and productive indicators prepared in a survey where the ODK-Collect application was used, giving the research the data in an SPSS format for subsequent analysis using an Excel spreadsheet and the modified Sarandón methodology, which consists of a systematization for the integration of the variables and the evaluation capable of integrating the dimensions to which ranges from 0 to 4 are given for the critical points present in the 3 provinces, obtaining the following results: from the 105 potato producers, 51% of the respondents are men, the same ones who are heads of household and who are dedicated to agriculture; therefore, the critical points of each indicator of two, five, and three with averages of 0.00; 0.19; 1.06; 1.19; 1.21 and 1.64, subsequently, these values are shallow; hence it is necessary to look for a strategy on how to improve them and as a serious recommendation to establish a type of link to the community together with the students of the Technical University of Cotopaxi to work in potato cultivation and improve their production and the economy of their producers.